Four New Records of Two Genera Balanophyllia and Cladopsammia (Anthozoa: Hexacorallia: Scleractinia: Dendrophylliidae) from Korea - Choi, Eunae; Song, Jun-Im (Animal Systematics, Evolution and Diversity, 2014)
The four species of the family Dendrophylliidae are newly recorded in Korea: Balanophyllia (Balanophyllia) cumingii Milne Edwards and Haime, 1848, Balanophyllia (Balanophyllia) vanderhorsti Cairns, 2001, Cladopsammia eguchii (Wells, 1982), and Cladopsammia gracilis (Milne Edwards and Haime, 1848). The two genera of Balanophyllia and Cladopsammia, to which the four species belong, are newly recorded in Korea. They were collected from the subtidal zones in Jeju-do Island, Korea by SCUBA diving from 1987 to 2012. This study aims to identify the four dendrophyllid species based on external and internal morphological characters including growth form, size, budding, and color of colonies, shape and size of corallites, columella, theca, and septa. Balanophyllia (Balanophyllia) cumingii is distinguished by its solitary growth form, small and low subturbinate corallite with enlarged calice, and expanded basal part, exsert first and second septa, and Pourtal$\acute{e}$ 수식 이미지s plan. Balanophyllia (Balanophyllia) vanderhorsti is characterized by its quasi-colonial growth form, subturbinate corallites with compressed calice, thick theca, and Pourtal$\acute{e}$ 수식 이미지s plan. Cladopsammia eguchii is characterized by its phaceloid growth form of compressed corallites basally united with common coenosteum, flat spongy columella, thick theca, and Pourtal$\acute{e}$ 수식 이미지s plan. Cladopsammia gracilis is distinguished by its phaceloid growth form of corallites basally united with common coenosteum, and pronounced Pourtal$\acute{e}$ 수식 이미지s plan forming flower patterns.